Method Development, Validation And Forced Degradation Studies Of Tolperisone Hydrochloride By Rp-Hplc Method In Bulk And Tablet Dosage Form - I.CAROLIN NIMILA,; P.BALAN,; N.CHIRANJEEVI,; V. UMA MAHESWARI,; M.KARTHIKEYAN, (International Journal of Pharma and Bio Sciences, 2011)
A simple, reproducible and efficient reverse phase high performance liquid chromatographic method was developed for estimation of Tolperisone hydrochloride in tablet dosage form. Formulation containing Tolperisone hydrochloride is used as centrally acting muscle relaxant. Chromatographic separations were carried out isocratically by reverse phase C18 column (Symmetry C18, 5μ, 250nm x4.6mm). The sample was analyzed using Acetonitrile: water in the ratio of 45:55(pH adjusted to 3.0 with Orthophosphoric acid) as mobile phase at flow rate of 1ml/min and detection at 260nm. The drug was subjected to oxidation, acid, alkali and photolytic degradation condition and the stressed samples were analyzed by proposed method. The retention time for Tolperisone hydrochloride was found to be 1.847min and the recoveries for dosage form were between 99.01 to 101.86 for brand I and 101.65 to 102.86 for brand II. Linearity was obtained in concentration range of 2-10μg/ml with correlation coefficient of 0.99628. The drug substance was found to be susceptible to stress condition of oxidation and more stable to acid, alkali and photolytic condition attempted. The result of the analysis was validated statistically and recovery studies confirmed the accuracy and precision of the proposed method.